REZA KARINA HUBUNGAN MUTU PELAYANAN ANTENATAL CARE DENGAN KEPUASAN IBU HAMIL DI PUSKESMAS PANTAI CERMIN KECAMATAN TANJUNG PURA TAHUN 2023 - REZA KARINA (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
ABSTRACT Quality health services are health services that must pay attention to four main elements. The four main elements are input, environment, process, and output. Based on a survey conducted at the Pantai Cermin Health Center, out of 10 pregnant women, 4 people said the services provided by midwives were appropriate and 6 people said the services provided by midwives were not appropriate. To assess the satisfaction of pregnant women, it is necessary to analyze the quality of antenatal care services with the satisfaction of pregnant women including reliability, responsiveness, assurance, empathy and physical evidence. This study aims to determine the relationship between the quality of antenatal care services and the satisfaction of pregnant women at the Pantai Cermin Public Health Center, Tanjung Pura District, in 2023. This research was a quantitative research that’s an analytic survey with a cross sectional design. Sampling was done by perposive sampling technique. The total sample in this research were 64 respondents. The data analysis used Chi-Square test and the Logistic Regression test. The results of the bivariate analysis showed that there was a relationship between the quality of antenatal care services, namely reliability with a value of p = 0.002, responsiveness with a value of p = 0.022, assurance with a value of p = 0.005, empathy with a value of p = 0.012 and physical evidence with a value of p = 0.022 with maternal satisfaction pregnant. The multivariate analysis showed that the factor most related to the satisfaction of pregnant women was the physical state variable with a value of p = 0.010. It is suggested that the employees of the Pantai Cermin Health Center are motivated to further improve service quality by holding regular meetings with implementing staff and as a reference for further researchers in the form of qualitative research both from quality assessment, satisfaction and also service delivery.